Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd008262
|View full text |Cite
|
Sign up to set email alerts
|

Cold-water immersion (cryotherapy) for preventing and treating muscle soreness after exercise

Abstract: BACKGROUND: Many strategies are in use with the intention of preventing or minimizing delayed onset muscle soreness and fatigue after exercise. Cold-water immersion, in water temperatures of less than 15 °C, is currently one of the most popular interventional strategies used after exercise. OBJECTIVES: To determine the effects of cold-water immersion in the management of muscle soreness after exercise. SEARCH METHODS: In February 2010, we searched the Cochrane Bone, Joint and Muscle Trauma Group Specialised Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(114 citation statements)
references
References 13 publications
5
100
0
9
Order By: Relevance
“…Previous studies confirm the high physiological demands of Futsal matches 10,11,20 . Nowadays many athletes and coaches habitually use CWI after intense training sessions or competitive matches expecting that this intervention will accelerate recovery 1,2 . To date, only one study has investigated recovery procedures in Futsal players 19 , but the sample were composed by young players, members of college Futsal teams.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies confirm the high physiological demands of Futsal matches 10,11,20 . Nowadays many athletes and coaches habitually use CWI after intense training sessions or competitive matches expecting that this intervention will accelerate recovery 1,2 . To date, only one study has investigated recovery procedures in Futsal players 19 , but the sample were composed by young players, members of college Futsal teams.…”
Section: Discussionmentioning
confidence: 99%
“…Yanagisawa et al 22 also did not observe a positive effect of CWI (15 min However, other investigations showed that CWI attenuates muscle soreness 4,5 . The recent meta-analyses conducted by Leeder et al 1 and Bleakley et al 2 showed that CWI is effective to alleviating muscle sore-ness after damaging exercise between 24h up to 96 h of its application. One mechanism that has been proposed to explain the attenuation of muscle soreness is that CWI causes reduction in muscle blood flow and tissue temperature, lowering the inflammation induced by high-intensity damaging exercise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apesar da sua recomendação clínica e seu amplo uso, há controvérsia e pouco respaldo científico sobre a real eficácia da crioterapia durante a regeneração muscular em humanos (50,51 A maioria dos estudos que investigaram a resposta inflamatória e o dano oxidativo associado à lesão musculoesquelética aguda tem sido realizada com modelos animais.…”
Section: Crioterapia Como Agente Terapêutico Após Lesão Muscularunclassified